Analysis of Factors Affecting Referral Rates in Community Health Centers: A Scoping Review - Juwita, Nanda Elok; Santoso, Dwi (BPJS Kesehatan, 2025)
The implementation of the National Health Insurance (JKN) in Indonesia has gone well, with the strengthening of primary care functions. One health facility that provides primary health care services owned by the government is the Community Health Center (Puskesmas). The target referral rate for Puskesmas in 2024 is a challenge to control. The high number of referrals can increase hospital visits and costs. Special efforts are needed to achieve these targets. This study aims to determine the factors affecting referral rates in community health centers. The study used a scoping review method. The literature search was conducted in the 2021-2024 range using Researchgate, PubMed, Google Scholar, and other sources. The keywords used were Primary Care, Referral Rate, and Community Health Centers. Literature selection resulted in eight articles that met the criteria for analysis. Some factors found were facilities and infrastructure, human resources, disease complications, drug availability, patient perceptions, location of community health centers, Standard Operating Procedures (SOP) for referrals, and applicable regulations. Fulfillment of these factors is necessary to achieve referral rates.